Designing Virtual Educational Environment in Light of Distance Learning Requirements to Develop Creative Teaching Skills for Faculty Members at University of Hail - Tamara Awad Kheder Alobeid Allah, Thanaa Abd Al Rasheed Muhammad Ibrahim, Seham Alsayed Saleh Murad, (Pakistan Journal of Medical & Health Sciences, 2022)
Summary of the Research: The current research aimed to design a virtual learning environment in light of the distance education requirements for the development of creative teaching skills among faculty members at the University of Hail. The descriptive analytical approach was used and an expert opinion poll was used about the list of distance education requirements and the list of creative teaching skills; The results of a questionnaire to identify needs, which were applied to a sample of (120) faculty members at the University of Hail, showed that all areas of training needs in the field of creative teaching are required and important, and that the degree of training need for creative teaching skills in Its five axes came to a large degree, of creative teaching and creative teaching skills related to fluency, flexibility and originality for the research sample. The teaching staff at the University of Hail is based on the requirements of distance education and is judged by specialists in training programs according to a special evaluation card to take into account the availability of technical and educational standards in its design.